Linear Matrix Inequalities Based State Feedback and Reference Feedforward Actuator Saturated H-infinity Control of Small-Scale Unmanned Helicopter - Sever, Mert; Goktas, Gulay; Yazici, Hakan; Kucukdemiral, Ibrahim Beklan (IEEE, 2015)
In this study, systematic procedure of the flight controller design for a small-scale unmanned helicopter is presented. The procedure is based on a linear dynamical model. The proposed controller is composed of state feedback and reference feedforward. Reference tracking performance is formulated in terms of L-2 gain from reference inputs to tracking errors and respective integral terms. Solution of the optimal controller with minimum L-2 gain is cast to the semi definite programming problem with a set of Linear Matrix Inequality (LMI) constraints. Six degree-of-freedom linear helicopter model with two degree of freedom rotor dynamics is used to illustrate the effectiveness of approach through simulations. Numerical simulations show that the stability of controlled system and boundedness of control signals against reference trajectories with bounded magnitudes are guaranteed by the proposed controller.
Keywords: DESIGN; SYSTEMS; Engineering